Learning to Critique Disability Children’s Literature Available to Teacher Candidates in Their Local Communities - Rieger, Alicja (Journal of the American Academy of Special Education Professionals, 2010)
This work reports on teacher candidates’ critique of disability children’s literature available to them in their local communities. Blaska’s (2003) Images and Encounters Profile: Checklist to Review Books for Inclusion and Depiction of Persons with Disabilities was used in order to maintain consistency among teacher critiques. The findings suggest that the teacher candidates experienced difficulties in locating disability children’s literature in their communities. The majority of the disability children’s books that they were able to review, however, met Blaska’s (2003) Images and Encounters Profile criteria. The teacher candidates’ perspectives related to the critique experience are also discussed, and a table of the reviewed disability children’s books is included.